Sensitivity to Structure in the Speech Signal by Children with Speech Sound Disorder and Reading Disability - Johnson, Erin Phinney (2011)
PURPOSE: Children with speech sound disorder (SSD) and reading disability (RD) have poor phonological awareness, a problem believed to arise largely from deficits in processing the sensory information in speech, specifically individual acoustic cues. However, such cues are details of acoustic structure. Recent theories suggest that listeners also need to be able to integrate those details to perceive linguistically relevant form. This study examined abilities of children with SSD, RD, and SSD+RD not only to process acoustic cues but also to recover linguistically relevant form from the speech signal. METHOD: Ten- to 11-year-olds with SSD (n = 17), RD (n = 16), SSD+RD (n = 17), and Controls (n = 16) were tested to examine their sensitivity to (1) voice onset times (VOT); (2) spectral structure in fricative-vowel syllables; and (3) vocoded sentences. RESULTS: Children in all groups performed similarly with VOT stimuli, but children with disorders showed delays on other tasks, although the specifics of their performance varied. CONCLUSION: Children with poor phonemic awareness not only lack sensitivity to acoustic details, but are also less able to recover linguistically relevant forms. This is contrary to one of the main current theories of the relation between spoken and written language development.